Intensive Care Unit admission and long-term survival in older patients after elective major noncardiac surgery: A secondary analysis - Yu-Jia Wu; Ya-Wei Li; Na-Ping Chen; Mo Li; Ya-Ting Du; Wei-Jie Zhou; Cong Fu; Ya-Fei Liu; Dong-Xin Wang (PLoS ONE, 2025)
Background Intensive care unit (ICU) admission after surgery is an important part of perioperative care but was found not effective in reducing perioperative mortality. This study was designed to test our hypothesis that ICU admission in older patients after elective major noncardiac surgery was not associated with improved long-term survival. Methods This was a secondary analysis of database from a previous trial and long-term follow-up. Patients were analyzed according to whether they were admitted to ICU after surgery or not. We used propensity score-matching to balance baseline, perioperative, and long-term variables and multivariable Cox proportional hazard regression to adjust confounding factors. Our primary endpoint was overall survival. Secondary endpoints included recurrence-free survival and event-free survival. Results A total of 1712 patients (mean age 69.5 years, 65.3% male, 91.9% cancer surgery) completed long-term follow-up (median 74 months) and were included in this secondary analysis. After propensity score matching, 464 patients remained in the matched cohort, with 232 patients in each group. At the end of follow-up, there were 112 deaths of 232 patients (48.3%) who were admitted to the ICU, compared with 111 deaths of 232 patients (47.8%) who were not: adjusted HR 1.08, 95% CI 0.83–1.41, P = 0.573. Secondary endpoints, including recurrence-free survival and event-free survival, also did not differ significantly between groups. Conclusions For older patients after elective major noncardiac surgery mainly for cancer, ICU admission was not associated with improved long-term survival. Studies are required to identify patients who would benefit from postoperative ICU admission regarding long-term outcomes.